Use of CMAP, MScan fit-MUNE, and MUNIX in understanding neurodegeneration pattern of ALS and detection of early motor neuron loss in daily practice. (10th January 2021) - Gunes, Taskin; Sirin, Nermin Gorkem; Sahin, Sevki; Kose, Ercan; Isak, Baris
Highlights: MUNIX and MScan-fit MUNE are useful in determining early motor unit loss. MUSIX is a reliable parameter in evaluation of re-innervation. In ALS, dying-back pattern of degeneration was considered for lower motor neurons. Abstract: Background: The pattern of lower motor neuron (LMN) degeneration in amyotrophic lateral sclerosis (ALS), i.e., dying-back (from the nerve ending to cell body) or dying-forward (from the cell body to nerve ending), has been widely discussed. In this study, we aimed to evaluate LMN loss using compound muscle action potential (CMAP), motor unit number index (MUNIX), and MScan-fit-based motor unit number estimation (MUNE) to understand the pattern of neurodegeneration in ALS. Methods: Twenty-five patients were compared with 25 controls using CMAP amplitude and area, MUNIX, and MScan-fit MUNE in three proximal and distal muscles innervated by the ulnar nerve. Results: Unlike the controls, the CMAP area, MScan-fit MUNE, and MUNIX recorded in ALS patients showed more neurodegeneration in distal muscles than proximal muscles. In ALS patients with unaffected CMAP amplitudes (n = 13), the CMAP area, MScan-fit MUNE, and MUNIX showed subtle motor unit loss of 30.7 %, 53.8 %, and 38.4 %, respectively. Conclusion: The CMAP area, MScan-fit MUNE, and MUNIX showed neurodegeneration earlier than the reduction in CMAP amplitude. These tests confirmed dying-back neurodegeneration, while only MUSIX showed re-innervation in ALS.